Introduction to information systems supporting and transforming business /cR. Kelly Rainer, Jr., Efraim Turban, Richard E. Potter ; with contributions by Dana Newton - Rainer, R. Kelly Jr. 1949-; Potter, Richard E. (John Wiley & Sons Singapore Pte.Ltd, 2015)
The goal of Rainer, Introduction to Information Systems 5e is to teach all business majors, especially undergraduate ones, how to use information technology to master their current or future jobs and to help ensure the success of their organization